Impact of Secondary and Micronutrients on Productivity and Quality of Bt Cotton: A Review - Swetha, D.; Laxminarayana, P.; Vidyasagar, G. E. C. H.; Reddy, S. Narender; Sharma, Harish Kumar (International Journal of Economic Plants, 2020)
Secondary and micronutrients are essential elements that are used by plants in small quantities. Yield and quality of agricultural products increased with secondary and micronutrients application, therefore human and animal health is protected.. Secondary (Ca, Mg, S) and micronutrients especially Zn, B are essential for higher productivity of cotton. Magnesium is essential for the production of the green pigment in chlorophyll, which is the driving force for photosynthesis. It is also essential for the metabolism of carbohydrates (sugars), for cell division and protein formation. Zinc is an element directly affects yield and quality because of functions such as activity in biological membrane stability, enzyme activation ability and auxin synthesis, while, boron plays an essential role in the development and growth of new cells in the growing meristem and also required for protein synthesis where nitrogen and carbohydrates are converted into protein. This article reviews the influence of Mg, Zn and B application on yield and quality aspects of Bt cotton.